TorakochirurgiaLobectomy or wedge resection? – The comparison of outcome in patients operated on for T1N0M0 non-small cell lung cancer - Bella, Mariusz; Kowalewski, Janusz; Dancewicz, Maciej; Świniarska, Joanna; Malinowski, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Surgical resection is a method of choice for the treatment of non-small cell lung cancer (NSCLC) in patients with stage T1N0M0. However, the range of resection necessary to achieve good long-term outcome is still a point of interest. Lobectomy is presently regarded as a golden standard but many authors report good long-term outcome after limited lung resections comparable to those observed after lobectomy. Aim: The aim of the study was to compare outcome in patients treated for NSCLC in stage T1N0M0 by lobectomy and wedge resection. Material and methods: 65 patients operated on for NSCLC in stage T1N0M0 between January 1999 and December 2005 were retrospectively analyzed. Lobectomy was performed in 51 patients and wedge resection in 14 cases. We evaluated overall survival, recurrence-free time, number of postoperative complications and the frequency of locoregional recurrences and distant metastases. Results: It was found that patients after lobectomy had significantly longer overall survival (43.4±21.6 vs. 28.5±10.7 months; p=0.032), longer recurrence-free time (31.8±26.2 vs. 15.2±11.4 months; p=0.014) and higher rate of 2- and 5-year survival. No significant differences were found in relation to the number of postoperative complications, locoregional recurrences or distant metastases between the groups. Conclusions: Wedge resection cannot be treated as an alternative method for lobectomy in the treatment of patients with T1N0 NSCLC due to worse long-term outcome.